Collaboration in Collections - Alvarenga Agustin, Damaris; Fader, Amy; Gagnon, Madison; Kaliebe, Mohala; Langbauer, Laurie; Mascenik, Mila; Parker, Caroline; Turi, Matt (Journal of Juvenilia Studies, 2025)
This essay presents a rough outline of the “what, how, and why” of the collaborative work done in English 425: “Literature, Archives, and Original Research,” an intensive research undergraduate course at the University of North Carolina at Chapel Hill in the Fall 2024 that focused on juvenilia. The team included a class of thirteen undergraduates (all years; all majors), five PhD students from English and Comparative Literature, one professor from the same department, instructional specialists from Ackland Art Museum, and librarians galore from Wilson Library Special Collections and Davis Library, all at UNC Chapel Hill. We met with two or three museum and four or five library colleagues; but many others, behind the scenes, made our course possible.Eight members of this team tell their story from the points of view of four students, three librarians, and the professor. The projects the class undertook show what can happen when participants believe in each other as partners. They also show how young researchers occupy an exceptional position when it comes to considering what young artists and authors care about and why it matters.